Die Canabae von Carnuntum II Archäologische und GIS-analytische Auswertung der Oberflächensurveys 2009-2010 - Gugl, Christian (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The Carnuntum canabae legionis holds a special place in the category of the civilian suburbs of Roman fortresses. An overall plan of the canabae now exists, thanks to the intensification of aerial-archaeological evaluations in recent years in the area of present-day villages of Petronell and Bad Deutsch-Altenburg (Lower Austria, A); its richness in detail makes it unique. The hope of obtaining additional evidence regarding the expansion and chronology of the settlement - as well as the use of municipal zones (such as residential, economic and funerary areas, and open spaces) - was linked to the idea of performing a large-scale surface survey.